Sustainable transportation systems : plan, design, build, manage, and maintenance : proceedings of the Ninth Asia Pacific Transportation Development Conference, June 29-July 1, 2012, Chongqing, China - Bai, Yong, 1963- (American Society of Civil Engineers, 2012)
Proceedings of the Ninth Asia Pacific Transportation Development Conference, held in Chongqing, China, June 29-July 1, 2012. Sponsored by International Chinese Transportation Professionals Association; T.Y. Lin International Group, China; Chongqing Urban Planning Bureau, China; Transportation & Development Institute of ASCE. This collection contains 81 papers describing innovations in the development of sustainable transportation systems. In the face of ongoing challenges such as traffic congestion, environmental degradation, and rising energy costs, transportation professionals look for new strategies, methods, and technologies to address issues of funding, planning, construction, and maintenance of transportation facilities of all types. These papers showcase both new approaches developed for China's enormous transportation infrastructure market and the latest advances in management and maintenance from researchers in the United States and other developed countries. Topics include: sustainable transportation development; low carbon emissions and energy saving in transportation; multimodal transportation systems; intelligent transportation systems; advancements in traffic control technologies; transportation and work zone safety; design and construction of bridges and tunnels; pavement materials, design, and construction; and geotechnical design and construction. This collection offers inspiration and practical solutions for engineers, planners, and managers working on transportation systems around the world.